Long Head of the Biceps Tendon (LHBT) - Robert C Manske; Michael Voight; Chris Wolfe; Phil Page (North American Sports Medicine Institute, 2022)
Pathology of the long head of the biceps brachii tendon (LHBT) is a common source of shoulder pain. While a careful history and a thorough physical examination are important steps in the assessment of LHBT pathology, it is still difficult to differentiate the type and severity of the pathology. Currently, the gold standard for confirming a diagnosis of LHBT pathologies is arthroscopic examination. Additionally, MRI is commonly ordered for diagnosis. Since an accurate diagnosis of pathology is critical for treatment success, musculoskeletal ultrasound (MSK US) is an attractive adjunct to the diagnostic process for long head of the biceps pathology due to it being safe, inexpensive and non-invasive. When used in combination with clinical special tests, MSK US can drastically increase the diagnostic accuracy of the clinical examination.